Application of Kahoot to Increase Students’ Physics Learning Motivation - Sahrin, Tedi (Universitas Negeri Makassar, 2024)
Abstract. This research aims to determine the increase in students' motivation to learn physics after implementing Kahoot in classroom learning. This type of research is Collaborative Classroom Action Research (PTK). This research was conducted at SMAN 2 Makassar with the research subjects, namely class X-3, totalling 36 students. Data collection was carried out in the odd semester of the 2023/2024 academic year using a physics learning motivation questionnaire test instrument, which was tested first using validity and reliability tests. The results of the research showed that there was an increase in students' motivation to learn physics in cycles I and II. In the pre-cycle, the percentage of students' motivation to learn physics was 54.34%, which was in the low category. Then, there was an increase in cycle I with a percentage of 76.95%, which was in the high category, and again increased in cycle II with a percentage of 83.70% in the very high category. Therefore, referring to the results of this research, the application of Kahoot can increase the motivation to learn physics of class X-3 participants at SMAN 2 Makassar Keywords: Kahoot, Learning Media, Motivation, Motivation to Learn Physics